Psychosocial, educational and communicative interventions for patients with cachexia and their family carers - Reid, Joanne (Curr Opin Support Palliat Care, 2014)
PURPOSE OF REVIEW: Cancer cachexia has a substantial impact on both patients and their family carers. It has been acknowledged as one of the two most frequent and devastating problems of advanced cancer. The impact of cachexia spans biopsychosocial realms. Symptom management in cachexia is fraught with difficulties and globally, there remains no agreed standard care or treatment for this client group. There is a need to address the psychosocial impact of cachexia for both patients and their family carers. RECENT FINDINGS: Patients living at home and their family carers are often left to manage the distressing psychosocial impacts of cancer cachexia themselves. Successful symptom management requires healthcare professionals to address the holistic impact of cancer cachexia. High quality and rigorous research details the existential impact of cachexia on patients and their family carers. This information needs to inform psychosocial, educational and communicative supportive healthcare interventions to help both patients and their family carers better cope with the effects of cachexia. SUMMARY: Supportive interventions need to inform both patients and their family carers of the expected impacts of cachexia, and address how to cope with them to retain a functional, supported family unit who are informed about and equipped to care for a loved one with cachexia.